Review – What is good research? - Wallén, Göran (NOMAD Nordic Studies in Mathematics Education, 1994)
Criteria for Scientific Quality and Relevance in the Didactics of Mathematics. Report from a symposium held in Gilleleje, Denmark, 1992. Editors: Gunhild Nissen and Morten Blomhøj. Danish Research Council for the Humanities. Roskilde University, IMFUFA. 1993. ISBN 87-7349-178-0, ISSN 0906-0103.